CTX-M type extended-spectrum β-lactamase in Escherichia coli isolated from extra-intestinal infections in a tertiary care hospital in south India - Rohit, Anusha (Indian J Med Res, 2019)
BACKGROUND & OBJECTIVES: Infections caused by extended-spectrum β-lactamase (ESBL)-producing Escherichia coli carrying bla(CTX-M) genes have been spreading globally, but there are geographical variations in the type of bla(CTX-M) genes prevalent and there are scanty data from India. This study was conducted to determine the CTX-M type ESBLs in E. coli isolates obtained from clinical specimens from patients with extra-intestinal infections attending a tertiary care hospital in south India. METHODS: ESBL-producing E. coli isolated from patients with extra-intestinal infections were subjected to PCR using CTX-M group-specific primers. From a representative isolate, full-length CTX-M-15 gene was amplified and sequenced. An internal fragment of this gene was sequenced in 10 representative isolates. RESULTS: Of the 300 isolates of E. coli tested, 88 per cent carried CTX-M genes and bla(CTX-M-15) was the most dominant gene present in 90 per cent of the positive isolates. Most (91%) of the isolates positive for bla(CTX-M) were sensitive to meropenem. INTERPRETATION & CONCLUSIONS: Our findings showed bla(CTX-M-15) to be the dominant gene. Based on the data on antimicrobial susceptibility, cefoperazone-sulbactum could be an antimicrobial of choice.